Effect of CO2-based binary mixtures on the performance of radial-inflow turbines for the supercritical CO2 cycles. (1st March 2023) - Yang, Yueming; Wang, Xurong; Hooman, Kamel; Han, Kuihua; Xu, Jinliang; He, Suoying; Qi, Jianhui
Abstract: Recently, the supercritical carbon dioxide (S CO 2 ) power cycle has become a hotspot in the field of energy-efficient utilization. The utilization of additives in the power cycle has been proven to be an effective way to improve the S CO 2 power cycle efficiency. As one of the core components of the system, the influence of CO 2 -based mixtures on turbine performance needs to be further explored. In this study, the preliminary design and three-dimensional numerical simulation of a 500 kW radial-inflow turbine (RIT) for small-scale S CO 2 power systems were carried out. Furthermore, the design and off-design performance of high Reynolds number and small size turbine under the change of the CO 2 -based binary mixture compositions and mixing ratios were studied. Increasing the amount of nitrogen, oxygen, or helium into CO 2 has a negative effect on the RIT performance, and the appropriate amount of xenon or krypton can improve the turbine efficiency. Moreover, mixtures with higher krypton additions adapt to higher heat source conditions. The loss of the turbine stage passage shows that a large amount of helium greatly reduces the working fluid density, and the high amount of xenon has a great influence on the dynamic viscosity, which all makes the RIT operation deviate from the steady state. Therefore, the CFD model simulation fails indicating that RIT designed based on pure CO 2 may not run smoothly and continuously. The losses in the stage with pure CO 2 and CO 2 –Kr mixture were investigated. The results indicate that the losses originated from the stator cannot be ignored and that the improvement of efficiency is mainly owed to the reduction in clearance losses. There is no doubt that the viewpoints proposed in this paper have significant reference value for the practical application of the S CO 2 power cycle using mixtures. Highlights: The design and performance of a SCO2 radial-inflow turbine were investigated. Real gas physical properties of mixtures applied to numerical simulations. Comprehensive CFD simulations and analyses for the turbine were performed. The effects of the mixture's properties on turbine performance were analyzed.